0726 Visceral adiposity and daytime sleepiness are associated with hypertension in mild-to-moderate sleep apnea: age-related differences. (25th May 2022) - Karagkouni, Efthalia; Vgontzas, Alexandros; Fernandez-Mendoza, Julio; Lenker, Kristina; Basta, Maria; Krishnamurthy, Venkatesh; Bixler, Edward
Abstract: Introduction: Mild-to-moderate obstructive sleep apnea (OSA) affects 15-40% of the adult general population and is associated with incident hypertension, particularly in young and middle-aged adults. We examined whether visceral adiposity, a key predictor of OSA, and excessive daytime sleepiness (EDS), a cardinal symptom of OSA, are associated with hypertension in middle-aged and older adult patients with mild-to-moderate OSA. Methods: A clinical sample of 148 adults (53.79±12.45y, 36.5% female) with mild-to-moderate OSA (5≤AHI<30) underwent 8-hour polysomnography, a clinical history and physical examination, including measures of blood pressure. EDS was defined as an Epworth Sleepiness Scale (ESS) score ≥11. Hypertension was defined as blood pressure ≥140/90mmHg or the use of anti-hypertensive medication. Visceral Adiposity Index (VAI) was calculated within each sex using Amato et al (2010) standardized formulas based on waist, BMI, triglycerides and HDL cholesterol. Logistic regression models examined the association between VAI, AHI and EDS with hypertension, adjusting for sex and stratifying by age. Under the receiver-operating characteristics (ROC) curves (AUC) with sex, BMI, AHI, VAI and EDS as independent variables examined predictive risk of hypertension. Results: VAI (OR=1.64, 95%CI=1.23-2.20, p=0.001) and EDS (OR=2.73, 95%CI=1.04-7.17, p=0.042), but not AHI (OR=1.05, 95%CI=0.98-1.13, p=0.165), were associated with significantly increased odds of hypertension in adults aged <60y (46.81±8.83y), while none of these associations were significant in adults aged ≥60y (67.06±5.65y). Adding VAI and EDS to standard clinical factors (age, sex, and BMI) yielded a strong risk model for hypertension in adults aged <60y (AUC= 0.80), and weaker in adults aged ≥60y (AUC=0.62). Conclusion: These data indicate that the combination of visceral adiposity and subjective sleepiness improves markedly the ability for clinicians to detect cases of mild-to-moderate OSA with increased cardiovascular risk, an association that is strongest in young and middle-aged adults. These findings also further support that OSA in older subjects is a distinctly different phenotype than in young and middle-aged adults. Support (If Any):